T2 and DWI in pilocytic and pilomyxoid astrocytoma with pathologic correlation - Horger, Marius; Vogel, Monika Nadja (The journal, 2014)
Objective:To quantify and compare T2 signal and apparent diffusion coefficient (ADC) in pilocytic and pilomyxoid astrocytoma (PA and PMA) and correlate results with myxoid content. Methods: Echo-planar diffusion weighted images (DWI) and standard magnetic resonance imaging (MRI) findings were reviewed retrospectively in patients with PA (n=34) and PMA (n=8). Regions of interest (ROIs) were drawn on ADC maps within tumor parts with lowest ADC values. Apparent diffusion coefficient values in tumor were normalized to those in cerebrospinal fluid (ADC/CSF). The ratio of T2 signal intensity in solid tumor parts to CSF (T2/CSF) was registered. Myxoid matrix was histologically quantified retrospectively in 8 PMAs and 17 PAs and correlated with imaging findings. Results: Mean ADC/CSF for PA and PMA was 0.53±0.10 and 0.69±0.10 (p<0.01). Mean T2/CSF for PA and PMA was 0.78±0.19 and 0.93±0.09 (p<0.01). Mean proportion of myxoid tumor matrix in PA was 50% (range, 10-100%) and 93% (range, 90-100%) in PMA (p=0.004). Eight patients (32%; all PA) had less than 50% myxoid content and 17 (68%; 8 PA; 9 PMA) had more. There was positive correlation of ADC/CSF, T2/CSF and ADC (r2=0.61, 0.65 and 0.60 respectively) and significant difference between the groups with more and less than 50% myxoid content (p=0.01 for ADC/CSF and T2/CSF and p=0.02 for ADC). Conclusions: General imaging features of PA and PMA are non-specific, ADC values and T2 signal intensity are generally higher in the latter, reflecting the proportion of myxoid matrix in these tumors.
Published online: 02 December 2014
Gesehen am 04.09.2018